Uso da língua eletrônica na avaliação de soluções ultradiluídas. - Laranjeira, Mateus Silva (Universidade Federal de São Carlos, 2011)
In this work it was used an electronic tongue constituted by ultrathin films of distinct materials deposited on gold interdigitated electrodes. According to the impedance measurements taken, it was tested if the device is able to differentiate highly diluted liquid systems. Solutions highly diluted and dynamically prepared were made at the laboratories of Faculdade de Ciências Farmacêuticas de Ribeirão Preto (USP) by Profa. Dra Marilisa Guimarães Lara. Experimental data acquisition was conducted by blind tests measurements involving samples with the same active principle (belladona) at distinct molar concentrations. We have made a comparison between conventional measurements taken at 1 kHZ and tan  values in addition to, in some cases, the tan  results favour the samples correlation throughout the Principal Component Analysis technique, by which it was possible the distinction of highly diluted solutions, with a good statistical correlation of the systems analysed. Moreover, it was made an in-situ impedance investigation during the growth of the layer-by-layer films used as sensing units, aiming a better comprehension of the fabrication process of these films onto interdigitated electrodes.
Keywords: filmes ultrafinos; materiais nanoestruturados; polímeros condutores; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA